A course module for the contemporary world - Botor, Nephtaly Joel B. (Manila : Rex Book Store, 2020)
"The contemporary world is a complex state, characterized by rapid scientific and technological advancements, colorful transfer of culture, and thriving economies. It is, therefore, a challenging feat to capture the nuances of the various issues, dimensions and manifestations of globalization into an instructional material such as this "Course Module on the Contemporary World."
Includes bibliography and index.
English text.
Keywords: Globalization